Cytokine Levels in Late Pregnancy: Are Female Infants Better Protected Against Inflammation? - Burns, Christine; Hall, Sharron Therese; Smith, Roger; Blackwell, Caroline (Frontiers in Immunology, 2015)
Inflammatory responses have been implicated in several forms of infant deaths (sudden expected deaths and stillbirths) and the initiation of preterm births. In this study we examined matched samples of term maternal blood, cord blood and amniotic fluid obtained from 24 elective Caesarean deliveries for both pro- and anti-inflammatory cytokines thought to be important in maintaining a balanced response leading to successful pregnancy outcome. These included interleukin (IL)-1β, IL-6, IL-8, tumour necrosis factor-α (TNF-α), interferon-γ (IFN-γ), IL-10 and IL-1 receptor antagonist (IL-1ra). Amniotic fluid levels for each of the cytokines examined were significantly higher than those for cord blood or maternal plasma. While pro-inflammatory cytokines were higher in amniotic fluid associated with male fetuses compared with females, the major significant difference was higher levels of IL-1ra in amniotic fluid associated with female fetuses. Our study supports similar findings for cytokines during mid-trimester which noted that amniotic fluid levels were higher than those in maternal blood. Our study suggests that maternal decidua secretes additional IL-ra in the presence of a female conceptus which improves the likelihood of a good outcome compared to pregnancies with a male fetus.